The transcription factor WRKY75 regulates the development of adventitious roots, lateral buds and callus by modulating hydrogen peroxide content in poplar. (16th November 2021) - Zhang, Yan; Yang, Xiaoqing; Nvsvrot, Tashbek; Huang, Liyu; Cai, Guanghua; Ding, Yiwei; Ren, Wenyu; Wang, Nian
Abstract: Hydrogen peroxide (H2 O2 ) plays important roles in plant development. Adventitious roots (AR), lateral buds (LB) and callus formation are important traits for plants. Here, a gene encoding RESPIRATORY BURST OXIDASE HOMOLOG B (PdeRBOHB) from poplar line 'NL895' ( Populus. deltoides × P. euramericana ) was predicted to be involved in H2 O2 accumulation, and lines with reduced expression were generated. H2 O2 content was decreased, and the development of adventitious roots, lateral buds, and callus was inhibited in reduced expression PdeRBOHB lines. A gene encoding PdeWRKY75 was identified as the upstream transcription factor positively regulating PdeRBOHB . This regulation was confirmed by dual luciferase reporter assay, GUS transient expression analysis and electrophoretic mobility shift assay. In the reduced expression PdeWRKY75 lines, H2 O2 content was decreased and the development of adventitious roots, lateral buds, and callus development was inhibited, while in the overexpression lines, H2 O2 content was increased and the development of adventitious roots and lateral buds was inhibited, but callus formation was enhanced. Additionally, reduced expression PdeRBOHB lines showed lowered expression of PdeWRKY75, while exogenous application of H2 O2 showed the opposite effect. Together, these results suggest that PdeWRKY75 and PdeRBOHB are part of a regulatory module in H2 O2 accumulation, which is involved in the regulation of multiple biological processes. Abstract : PdeWRKY75, PdeRBOHB, and H2 O2 accumulation form a regulatory loop which modulates the development of adventitious roots, lateral buds, and callus in poplar.